ANSIEDADE NA PERFORMANCE MUSICAL DE MÚSICA DE CÂMARA: O EFEITO DO BIOFEEDBACK COMO MEDIDA INTERVENTIVA - Barros, Samuel (2019)
Music Performance Anxiety (MPA) is described as a persistent apprehension that compromises performative skills, both in solo or group performances. In addition to physiological symptoms, such as increased heart rate, hyperventilation, sweating or nausea, MPA is associated with psychological and cognitive symptoms of performance negative impact. The present work intends to study the effectiveness of biofeedback training in the context of chamber music performance, applying a quasi-experimental. 2 quartets of trombonists were selected, quartet (1) being the experimental group and quartet (2) the control group. Both made public presentations, before and after the intervention. Quartet (1) underwent a program of 8 biweekly sessions of biofeedback training, in order to verify if it contributed to diminish the effects of MPA. The questionnaires State Trait Anxiety Inventory (STAI), Kenny Music Performance Anxiety Inventory (K-MPAI) and Kessler Psychological Distress Scale were used to evaluate the intervention efficacy. The results suggest that this type of intervention is favorable with regard to the decrease of APM levels in the context of chamber music. Some implications of this study are mentioned for the reduction of performance anxiety in training and teaching contexts, as well in professional musical practice.